Огненный бог Марранов: повесть-сказка / А. Волков - Волков Александр Мелентьевич (Юнацтва, 1992)
Экземпляры: ф. 4 (20120209) / Инвентарный номер: 98103 / Цена: 20.00 / Авт.знак: В 67 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6